2015
DOI: 10.2217/bmm.15.89
|View full text |Cite
|
Sign up to set email alerts
|

Micrornas as Pharmacogenomic Biomarkers for Drug Efficacy and Drug Safety Assessment

Abstract: Much evidence has documented that microRNAs (miRNAs) play an important role in the modulation of interindividual variability in the production of drug metabolizing enzymes and transporters (DMETs) and nuclear receptors (NRs) through multidirectional interactions involving environmental stimuli/stressors, the expression of miRNA molecules and genetic polymorphisms. MiRNA expression has been reported to be affected by drugs and miRNAs themselves may affect drug metabolism and toxicity. In cancer research, miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 242 publications
(230 reference statements)
2
62
0
Order By: Relevance
“…Recent studies have shown that miRNAs influence the expression of drug metabolizing enzymes (DMEs) (Jin et al 2016; Mohri et al 2010; Tsuchiya et al 2006; Wang et al 2017; Yu et al 2010, 2015a, b, c; Zeng et al 2017), which may thereby influence drug efficacy and safety (Koturbash et al 2015). miRNAs have been linked to liver injury and represent candidate biomarkers of liver injury because they are sufficiently stable in a wide range of biofluids, including serum (Baraniskin et al 2012; Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that miRNAs influence the expression of drug metabolizing enzymes (DMEs) (Jin et al 2016; Mohri et al 2010; Tsuchiya et al 2006; Wang et al 2017; Yu et al 2010, 2015a, b, c; Zeng et al 2017), which may thereby influence drug efficacy and safety (Koturbash et al 2015). miRNAs have been linked to liver injury and represent candidate biomarkers of liver injury because they are sufficiently stable in a wide range of biofluids, including serum (Baraniskin et al 2012; Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…By targeting at least 60% of all protein-coding genes, miRNAs are key regulators in the therapy strategy of cardiovascular diseases [47], neurological diseases [48], viral infection [49], etc . Meanwhile, miRNAs can target key metabolic enzymes or transporters mediating drug pharmacokinetics [50], adverse events and toxicity [5, 51]. In summary, we plan to develop more useful miRNA pharmacogenomic framework with a higher accuracy and robustness to identify more clinically relevant biomarkers for pharmacogenomic studies to speed up the development of precision medicine in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional pharmacogenomic studies focus on identifying which drugs will be the most effective with low toxicity for a particular patient harboring unique genetic profiles, such as single nucleotide polymorphisms, somatic copy number alterations or differential expressions of drug targets, drug-metabolizing enzymes or transporters [3]. Recent studies suggest that microRNAs (miRNAs) might play critical roles in pharmacogenomics [4, 5]. MiRNA pharmacogenomics is to study treatment responses at the miRNA level (Figure 1A): to decrease or increase the expressions of miRNAs, target genes or to change the activities of binding miRNAs [6].…”
Section: Introductionmentioning
confidence: 99%
“…This issue collected expert reviews which summarize recent efforts in the application of miRNAs as drug safety biomarkers for hepatotoxicity and cardiotoxicity testing [6][7][8]. Some miRNAs, such as miR-34a, miR-93-5p, miR-21 and miR-155, have demonstrated potential as biomarkers of nephrotoxicity [7,8].…”
Section: Micrornas As Noninvasive Biomarkers Have Tremendous Potentiamentioning
confidence: 99%
“…Studies have shown miRNAs to be potential biomarkers for identification of cancer patients who are likely resistant to specific treatment regimens [7]. Diagnosis of nonalcoholic fatty liver disease, especially determining its prognosis (from hepatic steatosis to nonalcoholic steatohepatitis), is a huge challenge in clinical practice because of the risks associated with the histologic examination method currently used.…”
Section: Special Focus Y Biomarkers In Regulatory Sciencementioning
confidence: 99%